A nanoindentation study of the viscoplastic behavior of pure lithium. (15th March 2017) - Wang, Yikai; Cheng, Yang-Tse
Abstract: Applying mechanical stresses is a possible approach to suppress dendrite and mossy lithium (Li) in Li metal electrodes. We conducted, in this work, nanoindentation tests on pure Li metal in an argon-filled glove box to study its viscoplastic behavior at room temperature. Both load-controlled and strain rate-controlled nanoindentations showed clear viscoplastic characteristics of Li. Based on an iterative finite element (FE) modeling approach, we determined a viscoplastic constitutive law for Li. In addition, we demonstrated by FE modeling that elastic modulus, on the order of GPas, has a negligible influence on the nanoindentation response of Li at ambient temperature. Graphical abstract: